The good news we almost forgot : rediscovering the Gospel in a 16th century catechism - DeYoung, Kevin (Chicago, IL : Moody Publishers, 2010)
Examines the sixteenth century Heidelberg Catechism, which focuses on the Apostle's Creed, the Ten Commandments, and the Lord's Prayer, and reinvents its teachings for a modern audience.
Includes bibliographical references.
Keywords: Heidelberger Katechismus; Reformed Church -- Catechisms